Designing Mobile Game “Tebak Kata Inggris” as the Media of Teaching Vocabulary for Primary School Students: A Development Research for Four Grade Students in SD Integral Luqman Al-Hakim Pontianak - Agus Supriadi; Gatot Sutapa; Clarry Sada (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study explores the development of an Android-based mobile game application, "Tebak Kata Inggris," designed to enhance English vocabulary learning for elementary students at Luqman Al-Hakim Qur'an-Based Integral Elementary School in Pontianak. Addressing the cognitive, affective, and psychomotor aspects of education, the research utilizes the MIT App Inventor software to create an engaging, user-friendly educational tool. The game aims to increase student motivation, engagement, and vocabulary proficiency by providing an interactive learning experience that can be accessed at school, home, or play areas. The findings suggest that mobile educational games can effectively supplement traditional teaching methods, making English learning more appealing and accessible for young learners. This approach aligns with the school's mission to develop linguistic competence alongside character education, leveraging technology to meet educational objectives more effectively.